: المنهج الاجتهادي عند المحقق سعيد بن خلفان الخليلي الإباضي دراسة أصولية تطبيقية - حارثي، سالم سعيد محمد (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
The jurist Sa‘id bin Khalfan al-Khalili is considered as one of the most prominent scholars in thirteenth century AH in Oman, and the reference scholar of fatwa in his time. Despite his great influence on the scientific and political life, his approach to Ijtihad, his methods of deducing the legal rules and his vision of Islamic politics were not adequately dealt with by research or discussion. This issue becomes more prevalent when it is realized that he does not include juristic terminologies in his fatwa except for a few. Therefore, this research seeks to explain the main and subsidiary evidence on which al-Khalili relies and the implications of the expressions that he adopts in the analysis of legal texts. Additionally, the research also to identify Shaykh Sa’īd’s visions, aims and purposes of Islamic law and its role to guide the legal deduction and the impact of all of these factors on weighing the textual evidence and considering the juristic opinions by paying attention to the nuances between them and the possibility of basing the rules upon them. All this is meant to reach fatwa in accordance with the will of Allah, Exalted is He. Thus, the researcher has followed the Ijtihadi approach of Shaykh al-Khalili, starting from adopting the evidence through the method of deduction, and reaching at the correct conclusion in fatwa. The importance of the research stems from the fact that al-Khalili was a jurist who had a great influence in politics at the 13th century. Thus, knowing his approach on Ijtihad, the balancing between interests and harms and consulting the purposes of Shari'ah would be a great help to jurists, scholars, and those involved in fatwá, especially with the contemporary raging political conflicts. The research study also highlights a methodology of Ijtihad within the Ibaḍi School of Law. In order to conduct this research, the researcher relied on the juristic and theological writings of Shaykh al-Khalili, applying the inductive analytical methodology by discussing his fatwas to find out his Uṣuli views, which ultimately lead to identifying the Ijtihadi approach of the al-Khalili. The researcher has concluded that al-Khalili was using the Uṣuli principles in order to reach the legal ruling, despite not explicitly stating those Uṣuli principles in most cases. Beside the use of the Uṣuli principles, he also relies on the unrestricted interests of Shari'ah. All that is meant to establish the State without compromising the prerequisites and the necessary conditions when taking concessions. It is noticeable that al-Khaili, has a distinguished jurisprudential consideration in the juristic nuances and understanding that helped him in fatwa in which he was known of observing moral conduct and considering the personal state of the questioner. The researcher recommends conducting in-depth studies in the juristic approach of Shaykh al-Khalili and making use of them in the fatwa institutions.